LIMITES E POSSIBILIDADES DOS PROCESSOS PEDAGÓGICOS CONTRIBUÍREM PARA O PROTAGONISMO CIDADÃO NO CONTEXTO DOS CENTROS DE REFERÊNCIA DE ASSISTÊNCIA SOCIAL – CRAS DOS CAMPOS GERAIS - Souza, Cristiane G. de (2017)
This research has as its object the pedagogical processes that empower the citizen in the context of the Centers of Reference of Social Assistance (CRAS) located in the small and medium-sized municipalities that belong to the area covered by the Regional Office of the Family and Social Development Secretariat (SEDS) located in the city of Ponta Grossa-PR. Social assistance must offer a series of services aimed at contributing to the autonomy and citizenship of the users of its services, with a view to becoming protagonists. In view of the conservative historical marks still present in the area and in the professional practices in the area of social assistance, the challenge is to understand the process of constitution of protagonism and citizenship, to perceive the possibilities and historical limits that are placed in the context of CRAS to develop strategies and actions to exercise citizen protagonism. Regarding the approach, this research is of a qualitative and quantitative nature, therefore of mixed focus. The city of Ponta Grossa is home to the Regional Office, and belongs to its area of coverage totaling 18 municipalities. The 17 municipalities that participated in the research were: Arapoti, Carambeí, Castro, Imbaú, Ipiranga, Ivaí, Jaguariaíva, Ortigueira, Palmeira, Piraí do Sul, Porto Amazonas, Reserva, São João do Triunfo, Sengés, Telêmaco Borba, Tibagi and Ventania. According to SUAS guidelines, the professional reference team working at CRAS is composed of an interdisciplinary team: Social Worker, Psychologist and preferably Pedagogist. The National Social Assistance Policy (PNAS) challenges these professionals to develop their practice in order to contribute to the process of citizen protagonism of users. Thus, it was necessary to describe the capitalist mode of production contextualizing the current sociability and its limits together with the process of protagonism and citizenship. We address the state and its role within social policies. We contextualize SUAS in the scope of Social Security and the constitution of Basic Social Protection in Brazil. We characterized the organization of Basic Social Protection in the small and medium-sized municipalities located in the region covered by the Regional Office of SEDS in the city of Ponta Grossa-PR. We characterized the constitution of the CRAS interdisciplinary teams and reflected on the process of strengthening the exercise of citizen protagonism based on the professional practices exercised by such teams. We defend the thesis that: since the teams need to carry out their professional practice by providing the citizens with a leading role, in this context actions must be carried out through pedagogical processes that take into account the reality, the demands of these users and the limits and possibilities that such Professionals in the development of such practices. In the sense of Gramsci, given the conditions of subalternity in which the working class is, the possibility of confronting this circumstance implies actions whose presupposition is a pedagogical process guided by the philosophy of praxis. It seeks to make explicit that subordinate behavior is forged by the ruling class, but that it can be confronted by access to knowledge that is not neutral, which will always be in harmony with the various corporate projects present within a society.